Study on Mitochondrial ATPase6 Gene Polymorphisms as a Genetic Risk Factor for Breast Cancer in Bangladeshi Women - Mohammad Islam; Gazi Sultana; Robin Khan; Ariful Islam; Hasan Mahmud; Sheikh Raihan (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Background and aim: Mitochondria play a vital role in cellular energy production and apoptosis; thus, it has a critical role in cancer development. This study aimed to evaluate polymorphisms in the mitochondrial ATPase6 gene as a genetic risk factor for breast cancer in Bangladeshi women. Materials and method: ATPase6 gene of mtDNA from sixteen breast cancer blood samples were sequenced to evaluate polymorphisms in the targeted gene. Polymorphisms are detected by comparing the sequences with the Revised Cambridge Reference Sequence (rCRS). Twelve blood samples from age-matched healthy women were also sequenced as a control to consider regional variations. Results: The A8812C polymorphism (p= 0.0085; from Fisher Exact Test) was found in 50% of breast cancer patients. The A8812C variation (novel mutation) substitutes the Threonine (T) to Proline (P) at the 96th codon number. The PolyPhen-2 analysis predicted that, with a score of 0.999, this variant is "probably damaging." The second prediction performed by the PROVEAN program showed that, since it has a score of -5,110 (<-2,5), this substitution is "Deleterious." These data indicate that A8812C might be associated with an increased risk of breast cancer indirectly. Another interesting finding is the frequent presence (56%) of A8701G in cancer patients (p= 0.0159; from Fisher Exact Test). Based on the statistical data, this (A8701G) mutation might relate to breast cancer development.  Conclusion: It can be concluded that mutations in the ATPase6 gene, especially the A8812C polymorphism and A8701G polymorphism, can be biomarkers for breast cancer diagnosis.